2002
DOI: 10.1016/s0736-0266(02)00032-3
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon healing: Long‐term biomechanical effects of postoperative mobilization and immobilization in a new mouse model

Abstract: The aim of the study was to investigate the long-term effects of postoperative immobilization as opposed to mobilization on the biomechanical attributes of healing Achilles tendons in a new experimental mouse model. Postoperative mobilization resulted in a continuous and significantly more rapid restoration of load to failure in comparison to the immobilization group. Tendon deflection was decreased by postoperative mobilization, whereas under immobilization it paradoxically increased still further in the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 19 publications
2
91
2
1
Order By: Relevance
“…As long as the muscle is relaxed and pliable, traction forces in the tendon callus should be low. Earlier models have used immobilization (Murrell et al 1994, Ishida et al 1996, Iwuagwu and McGrouther 1998, Yamamoto et al 1999, Palmes et al 2002, Matsumoto et al 2003. In animals, it is unclear to what extent immobilization really leads to unloading.…”
Section: Discussionmentioning
confidence: 99%
“…As long as the muscle is relaxed and pliable, traction forces in the tendon callus should be low. Earlier models have used immobilization (Murrell et al 1994, Ishida et al 1996, Iwuagwu and McGrouther 1998, Yamamoto et al 1999, Palmes et al 2002, Matsumoto et al 2003. In animals, it is unclear to what extent immobilization really leads to unloading.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments clearly showed that increased physical activity accelerated the healing process in agreement with earlier published studies. [35][36][37] Maximum activity level represented by the wheel-running group was found to result in the greatest diameter of organized collagen. The diameter at 4 weeks corresponded to that reached at 14 weeks in the control group, that is, in the freely moving rats of the longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is supported by several animal models, in which early motion accelerates the repair process and results in superior tissue quality 128 . Twaddle and Poon found comparable functional results and no significant difference in rerupture rate when controlled early motion was instituted following immobilization for ten days in patients treated with or without surgery 129 .…”
Section: Clinical Applicationsmentioning
confidence: 99%